GIS-Based Analysis of Distribution Patterns and Underlying Motivations of Prehistoric Settlements in the Middle and Lower Yuanjiang River Basin, Central China - Guifang Yang; Changhong Yao (Applied Sciences, 2025)
Exploring prehistoric settlement patterns and their relationship to natural environments is a key focus in geological research, particularly in historically significant regions. The middle and lower reaches of the Yuanjiang River in northwestern Hunan Province are central to the development of early civilizations. Unlike previous studies that focused on individual sites, this research analyzed settlement distribution and migration trends across the entire catchment area. Combining field research with geological, geomorphological, archaeological, remote sensing data, and Geographic Information System techniques, the study revealed a clear pattern: prehistoric settlements increased from higher elevations to lower areas in the east, with concentrations along rivers, especially at river junctions. High floodplains and terraces, offering flat terrain, abundant water, and rich vegetation, were key to supporting early communities. The analysis showed that climate change significantly impacted prehistoric occupations, limiting population growth and stability due to natural disasters. A regional comparison within the Yuanjiang basin indicated that ancient cultures in the downstream area were more similar to those of the Lishui River Basin, while the Wushui cultural group in the middle reaches displayed distinct differences. These findings highlight the complex relationship between geography and cultural development, with the lower reaches being more influenced by climatic fluctuations and natural disasters, especially during the Shijiahe and Shang-Zhou periods. Additionally, the middle reaches of the Yangtze River may have originated in the Xiajiang Area and shifted southward, leading to the rise of cultural centers in the Lishui River Basin. These results emphasize the significance of the Yuanjiang River catchment in Hunan Province in shaping ancient cultures and offer insights for contemporary sustainable practices.